SISTEM PENGENDALIAN RISIKO OPERASIONAL PADA BANK PERKREDITAN RAKYAT DENGAN PENDEKATAN INDIKATOR DASAR - Sunarjo, Sunarjo; Yuniarti, Sari (University of Merdeka Malang, 2017)
BPR as the micro financial medium institution was seen as one of the translation media and risk transformation. The ability of BPR in managing risk became attention along with the increase of volume and the business operational complexity, including bank operational risks like fraud caused by people, system, or external condition. If there was no controlling, it would create loss potency for BPR itself. This research aimed to measure the loss effect because of operational risk and to identify the system of operational risk control using basic indicator approach. The population of this research was all BPR in Malang, namely 39 banks. The samples used were 20 banks. Data collection method used was observation and documentation. The research result showed that operational risk events were divided into 4 quadrants, namely Low Frequency/High Impact, High Frequency/High Impact, Low Frequency/Low Impact, and High Frequency/Low Impact. The quadrants division resulted in information related to how the operational risk would be managed. The total capital charge of all BPR in Malang was IDR.4.085.114.000,00. It indicated that the total capital charge used was to anticipate the operational risk.